Antimicrobial efficacy of Punica granatum Lythraceae peel extract against pathogens belonging to the ESKAPE group - Scaglione, Elena; Sateriale, Daniela; Mantova, Giuseppe; Di Rosario, Martina; Continisio, Leonardo; Vitiello, Mariateresa; Pagliarulo, Caterina; Colicchio, Roberta; Pagliuca, Chiara; Salvatore, Paola (Frontiers in Microbiology, 2024)
The improper use and abuse of antibiotics has led to the increase of multi-drug resistant (MDR) bacteria resulting in a failure of standard antibiotic therapies. To date, this phenomenon represents a leading public health threat of the 21st century which requires alternative strategies to fight infections such as the identification of new molecules active against MDR strains. In the last twenty years, natural extracts with biological activities attracted scientific interest. Following the One Health Approach, natural by-products represent a sustainable and promising alternative solution. Consistently, the aim of the present study was to evaluate the antimicrobial activity of hydroalcoholic pomegranate peel extract (PPE) against MDR microorganisms belonging to Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa and Enterobacter spp. “ESKAPE” group pathogens. Through semiquantitative and quantitative methods, the PPE showed effective antimicrobial activity against Gram-positive and Gram-negative MDR bacteria. The kinetic of bactericidal action of PPE highlighted that the microbial death has been achieved in a time- and dose-dependent manner. High concentration of PPE exhibited antioxidant activity, with a protective effect on cellular system and on red blood cell membranes. Lastly, we report, for the first time, a significant intracellular antibacterial property of PPE as highlighted by its bactericidal action against the staphylococcal reference strain and its bacteriostatic effect against clinical resistant strain in HeLa cell line. In conclusion, due to its characterized content of polyphenolic compounds and antioxidant activity strength, the PPE could be considered as a therapeutic agent alone or in conjunction with standard antibiotics against challenging infections caused by ESKAPE pathogens.